Implementation of Digital Archive Storage Procedures in Event Secretarial Activities at the Polbeng Business Expo Chapter Two - Aulia, Bella Try; Astari, Yanisha Dwi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Digital archive storage procedures play a critical role in supporting administrative coordination and documentation continuity during event implementation. This study aims to analyze how digital archive storage procedures are applied by event secretaries at the Polbeng Business Expo Chapter Two. A descriptive qualitative approach was employed with data collected through interviews, observation, and documentation. The analysis was guided by seven storage indicators proposed by Read & Ginn, namely inspecting, indexing, coding, cross-referencing, sorting, storing, and retrieving. The findings show that event secretaries implemented digital archive procedures in a structured manner by conducting document inspection before storage, applying consistent file naming and categorization systems, grouping documents based on activity needs, and applying digital-based coding methods. Secretaries also stored documents using cloud storage platforms combined with local device backups to ensure accessibility and archive security. The implementation of these procedures facilitated information distribution, report preparation, and administrative coordination among committee members during the event. However, the study also found variations in the consistency of indexing and coding practices across different secretaries due to differences in digital literacy and the absence of formal procedural guidelines. Overall, this study demonstrates that Read & Ginn’s archival model can be effectively adapted within digital event contexts and provides insight into the role of digital archives in supporting administrative performance in non-government organizational environments.